1949
DOI: 10.1177/001316444900900105
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of "Validity" and "Reliability" as Applied to Sociometric Tests

Abstract: IT IS the purpose of this paper to attempt a clarification of the meaning of the terms &dquo;validity&dquo; and &dquo;reliability,&dquo; as they may be applied appropriately in an evaluation of sociometric tests. These instruments are being employed increasingly in educational and psychological research, having been in wide use by sociologists for a number of years. It is their intention to focus on an analysis of the individual as a member of a group, rather than on the individual as an entity in isolation.It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1953
1953
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…However, in 1949, Pepinsky already stated that the dynamic nature of social relations causes fluctuations in sociometric data over any period of time. Such fluctuations reflect actual changes in behaviour and group relations rather than the unreliability of the measure (Pepinsky, 1949;Ramsey, 1995). A similar idea is advocated by a group of scholars working in dynamic systems theory (see for instance Fogel, 1993;Thelen & Smith, 1994;Van Geert, 1994;and Van Geert & Steenbeek, 2005, for an overview).…”
Section: Stability Variability and Reliabilitymentioning
confidence: 87%
See 2 more Smart Citations
“…However, in 1949, Pepinsky already stated that the dynamic nature of social relations causes fluctuations in sociometric data over any period of time. Such fluctuations reflect actual changes in behaviour and group relations rather than the unreliability of the measure (Pepinsky, 1949;Ramsey, 1995). A similar idea is advocated by a group of scholars working in dynamic systems theory (see for instance Fogel, 1993;Thelen & Smith, 1994;Van Geert, 1994;and Van Geert & Steenbeek, 2005, for an overview).…”
Section: Stability Variability and Reliabilitymentioning
confidence: 87%
“…In spite of its importance, very little research has been done about the stability of given ratings of children (Pepinsky, 1949;Bukowksi & Newcomb, 1984;Terry, 2000). Duncan and Cohen (1995) found that in grade 1, 3, 6 and 8, children of the same gender rated each other higher than children of the opposite gender and popular children gave higher ratings than children of other sociometric groups.…”
Section: Stability Of Given Ratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…h performs the same function for the square matrix of sociometric ranks. This anpears to meet Pepinsly's demand for a measure of reliability of sociometrics , in the sense of consistency over judges (7). No splitting of the group into chance halves is required.…”
Section: "mentioning
confidence: 99%
“…The problem of splitting a sociometric test into two equivalent halves rules out the use of split-half reliability. A discussion at greater length of these points may be found in Pepinsky (1949) and Gronlund (1959). The most important questions seem to be concerned with ways of eliciting true choices at any time and with the stability of choices at different ages and under varying conditions.…”
Section: Validity and Reliabilitymentioning
confidence: 99%